2017
DOI: 10.3389/fmars.2017.00075
|View full text |Cite
|
Sign up to set email alerts
|

Congruent Molecular and Morphological Diversity of Macaronesian Limpets: Insights into eco-evolutionary Forces and Tools for Conservation

Abstract: Combined analysis of genetic and morphological variation can provide synergistic insights into eco-evolutionary forces shaping biodiversity, as well as tools for conservation and management. Macaronesian limpets are undergoing severe declines due to overexploitation which calls for an evaluation of the evolutionary significance and taxonomic status of populations. This study details the analysis of genetic (mtDNA sequencing) and morphological (geometric analysis of shell shape) variation among Macaronesian pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…The ability of wing traits to capture a genetic pattern so strikingly similar to that inferred from hundreds of molecular loci spread across the 16 honey bee chromosomes [35,52] could be explained by a high heritability and a polygenic nature of wing shape. While the genetic basis of forewing venation is virtually unknown in most insects, including honey bees, it is likely that wing shape has a strong genetic control, as suggested by this and other studies which have also reported concordance between wing morphology and molecular markers, such as mtDNA and microsatellites [78][79][80][81][82][83].…”
Section: Discussionsupporting
confidence: 54%
“…The ability of wing traits to capture a genetic pattern so strikingly similar to that inferred from hundreds of molecular loci spread across the 16 honey bee chromosomes [35,52] could be explained by a high heritability and a polygenic nature of wing shape. While the genetic basis of forewing venation is virtually unknown in most insects, including honey bees, it is likely that wing shape has a strong genetic control, as suggested by this and other studies which have also reported concordance between wing morphology and molecular markers, such as mtDNA and microsatellites [78][79][80][81][82][83].…”
Section: Discussionsupporting
confidence: 54%
“…This timing is within the range of other limpet taxa, including species of the same genus with 4–15 days (Ribeiro, 2008; Guallart et al ., 2020; Ferranti et al ., 2021), as well as the genera Cellana with 4–6 days (Mau et al ., 2018) and Lottia with 6–12 days (Kay & Emlet, 2002; Nakano et al ., 2020). Although the timing for development in limpets is specific and temperature dependent (Ribeiro, 2008; Ferranti et al ., 2021), the short duration of the larval stages implies a limited dispersal phase, explaining the genetic and morphometric differences observed between the Macaronesian and continental populations (Côrte-Real et al ., 1996 a , 1996 b ; Weber & Hawkins, 2005; Carreira et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(2018). Congruent patterns of variation at genetic and ontogenetic markers have been shown to be highly informative with respect to stock structure analysis (Carreira et al ., 2017; Gwilliam et al ., 2018; McKeown et al ., 2015, 2017) and in this case suggest the existence of demographic stock structuring within both regions which should be recognised in spatial management strategies (Reiss et al ., 2009). Key to this will be elucidation of stock isolating mechanisms and the relative roles of physical vs .…”
Section: Discussionmentioning
confidence: 99%